YAP1 inhibits the induction of TNF‐α‐stimulated bone‐resorbing mediators by suppressing the NF‐κB signaling pathway in MC3T3‐E1 cells. Issue 5 (22nd October 2019) - Yang, Beining; Sun, Hualing; Xu, Xiaoxiao; Zhong, Heli; Wu, Yanru; Wang, Jiawei
Abstract: Yes‐associated protein 1 (YAP1), the core downstream effector of the Hippo signaling cascade, was involved in the regulation of osteoblast and osteoclast differentiation and in bone metabolism. However, the regulatory effects and mechanisms of YAP1 on bone‐remodeling molecules in osteoblasts under inflammation remain unknown. In this study, YAP1 expression level was downregulated after treatment with inflammatory cytokine tumor necrosis factor‐α (TNF‐α) in MC3T3‐E1 cells. The key osteoclastogenic molecules induced by TNF‐α, namely, interleukin‐6 and receptor activator of nuclear factor‐κB (NF‐κB) ligand, were suppressed after lentivirus‐induced YAP1 overexpression, which dramatically increased the expression level of osteoprotegerin. Conversely, the expression levels of the above factors showed opposite trends in the YAP1 small interfering RNA and YAP1 inhibitor (verteporfin) group. Mechanistically, YAP1 attenuated the TNF‐α‐induced activation of the NF‐κB signaling pathway as revealed by the reduced expression of phosphorylated‐p65 and NF‐κB reporter activity and the nuclear translocation of p65. Moreover, the expression level of YAP1 suppressed by TNF‐α was reversed by berberine in concentration‐dependent manner. Taken together, our study suggests that YAP1 plays a critical role in the regulation of bone metabolism and is a potential therapeutic target for treating inflammatory bone resorption. Abstract : Figure 8 Schematic of the regulatory effects of yes‐associated protein 1 (YAP1) in osteo‐inflammatory mediator expression in MC3T3‐E1 cells in response to tumor necrosis factor‐α stimulation. YAP1 suppressed the nuclear factor‐κB signaling pathway, resulting in the decreased expression of bone resorption factors.